Asmat Indigenous Participation in Development through Participatory Mapping: : A Political-Anthropological Reflection - Hada, Hendrikus; Poli , Agustina Ivonne (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2025)
This study describes the process of participation of the indigenous people of the Asmat group of Pomar Sirau in participatory mapping and analyzes their participation rate based on the Arnstein Degree of Participation. Using a qualitative approach with a case study method, data was collected through in-depth interviews, participatory observations, Focus Group Discussions (FGDs), and document studies. The results of the study show that community participation takes place through several stages, starting from community awareness of threats to customary lands, community initiatives in voicing problems, to active involvement in mapping customary territories. Based on the Arnstein Degree of Participation, community participation is at the level of "Citizen Power," where they have full control over the mapping and decision-making process related to indigenous territories. This study confirms that participatory mapping is an important instrument in the protection of customary rights and cultural identity of indigenous peoples. It is hoped that there will be policy support, community capacity building, collaboration with various parties, and knowledge regeneration to ensure the protection and sustainability of the rights and culture of the indigenous people of Asmat.